POSITIONING STRATEGIES IN THE FORMATION AND DEVELOPMENT OF ARGICULTURAL REGIONAL BRANDS - BUDNIKEVYCH, Iryna; BURDYAK, Oleh (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article discusses agricultural regions (agrarian regions) as unique spatial entities which economies and strategic development are tied to agriculture. It highlights that marketing strategies for positioning the brand of an agrarian region increase its recognizability and attractiveness compared to competing territories, strengthening its reputation in national and international markets. The purpose of the article is to define the essence and specifics of the brand of agricultural regions, identify positioning strategies for these brands in their formation and development processes. The brand of an agricultural region is defined as a comprehensive concept, a composition of uniqueness, values, associations, advantages, and benefits that distinguish this region from others, creating its positive and memorable image for defined target audiences. It is noted that the immanent components, their properties, and the uniqueness of the agricultural region allow for the formation and maintenance of its brand. It is stated that the specifics of the agricultural region’s brand lie in the fact that it is built on the basis of the region’s spatial, natural-climatic, socio-cultural, and economic features; it includes key components such as resources, products, infrastructure, visuals, innovation, marketing, image-reputation, historical and value aspects. Understanding positioning as the process of creating and implanting a certain image of the agricultural region in the minds of target audience, two main directions of positioning strategies are identified and described: targeting consumers of a specific product, which forms the basis of the brand; targeting potential business partners. It is concluded that agricultural regions whose brands are oriented towards end consumers position themselves as territories that can offer a unique product, special conditions for familiarization with the product and conditions for its consumption, tourist and excursion support, emotional enrichment of the process, etc. In marketing strategies for positioning and promoting brands of this type, various communication channels, active tourist support of brands, and the creation of exclusivity in the sales of the basic product outside the region are actively used. Positioning that is aimed at potential business partners presents the agricultural region as an industrial-agricultural territory with "inclusions" of authentic traditionally agrarian enclaves aimed at preserving and demonstrating traditional ways of life, crafts, folk trades, etc. Marketing strategies focus on promoting the innovation of the agricultural region, readiness for further development, attracting investments in agricultural production development, and inviting new partners for cooperation. It is concluded that agricultural regions, in addition to positioning strategies aimed at end consumers and potential business partners, form alternatives that fit into the concept of innovation and sustainable development of the agricultural sector, tourism, and the hospitality industry, targeting new generations of consumers. An alternative type of positioning for an agricultural region is creating an image of a territory where the dominance of agricultural products in the gross regional product is based on the concept of sustainable development, ensured by the wide implementation of advanced technologies, industrial production methods in crop and livestock farming, intensification and digitization of the sector, etc. The characteristic features of such regions are defined as investments in technology and innovation; continuous improvement of infrastructure for production, processing, and sale of products, development of agricultural logistics; sustainable regional development and agroecology; image, reputation and trust, public opinion, positive perception of regional enterprises by consumers and partners, ecological and ethical reputation of the region, positive interaction experience with regional products, and others.